Analysis Of Apm (Anjungan Pendaftaran Mandiri) System Services On Outpatient Patient Satisfaction At Gambiran Hospital, Kediri City - Prisca Awanda; Ardi Bastian; Amarin Yudhana; Wening Palupi Dewi; Wahyu Purnomo Jati (Journal of Hospital Management and Services, 2024)
APM is a hospital innovation to improve service quality so as to increase patient satisfaction, which allows general patients who have been registered and whose requirements have been verified to be correct to register and receive a SEP (Participant Eligibility Letter) without having to go through the registration counter so that the registration process can be done in a short time. The purpose of the study was to analyze the effect of APM system services on outpatient satisfaction at Gambiran Hospital, Kediri City. This study used a quantitative observational design with a cross-sectional approach conducted in outpatient care at Gambiran Hospital, Kediri City. The population in this study were 1000 outpatients at Gambiran Hospital, Kediri City. The sample of this study was 286 people taken using a purposive sampling technique with the criteria of family/patient users of APM. The independent variable is the APM system service, while the dependent variable is outpatient satisfaction. Data collection used a questionnaire and analyzed using a person correlation test. The results of the Pearson correlation analysis test with p value = 0.000 and a correlation of 0.443, which means that there is a significant and positive relationship and sufficient strength of the relationship between the self-registration kiosk system service and the quality of outpatient patients at Gambiran Hospital, Kediri City. To improve patient satisfaction, adequate, innovative and up-to-date facilities are needed, supported by good human resources.